IMPLEMENTASI FINITE STATE MACHINE DALAM GAME EDUKASI BAHASA JEPANG - Saputra, Juan; Handoko, Koko (Computer Science and Industrial Engineering, 2024)
The development of technology enables people to immerse themselves in Japanese culture, encompassing aspects such as fashion, culinary, arts, and language. This influence has sparked a rapid increase in Indonesian interest to learn Japanese. However, it is undeniable that few schools include Japanese language courses in their curriculums, this circumstances forces students to seek alternative learning sources such as private tutoring or courses. Moreover, traditional learning methods often leave students feeling bored dan exhausted, particularly through textbooks, thus demanding more engaging and relaxed learning approaches. Solas School of Languages, located in Batam, offers various language courses including Japanese. This study aims to implement the finite state machine method into an educational Japanese language visual novel game for Android, designed using Ren’Py game engine. This method will be applied to alter NPC character expressions within the game. The research output includes an educational Japanese language game featuring implemented finite state machines, the appearance of its interface, and data collected directly from students learning Japanese at Solas School of Languages. Thus, it is hoped that this research will demonstrate the effectiveness of game-based learning methods in making studying more engaging and assisting teachers in educating their students outside classroom.